2000
DOI: 10.1103/physrevb.62.5619
|View full text |Cite
|
Sign up to set email alerts
|

Charge, orbital, and magnetic order inNd0.5Ca0.5MnO3<

Abstract: In the manganite N d 0.5 Ca 0.5 M nO 3 , charge ordering occurs at much higher temperature than the antiferromagnetic order (T CO = 250K, T N = 160K).the magnetic behavior of the phase T N < T < T CO is puzzling: its magnetization and susceptibility are typical of an antiferromagnet while no magnetic order is detected by neutron diffraction.We have undertaken an extensive study

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
91
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 23 publications
20
91
3
Order By: Relevance
“…The charge ordering traps out mobile holes, so the magnitude of α(T) increases sharply on cooling through T CO , and a further increase on cooling through T N indicates a long-range T OO ≈T N in this material. Independent neutron-diffraction experiments 15 have revealed that short-range orbital ordering increases on cooling in the interval T N <T<T CO . The CO and short-range orbital order appear to introduce a frustration that suppresses long-range magnetic order, which is why long-range T OO ≈T N .…”
Section: Iii-results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge ordering traps out mobile holes, so the magnitude of α(T) increases sharply on cooling through T CO , and a further increase on cooling through T N indicates a long-range T OO ≈T N in this material. Independent neutron-diffraction experiments 15 have revealed that short-range orbital ordering increases on cooling in the interval T N <T<T CO . The CO and short-range orbital order appear to introduce a frustration that suppresses long-range magnetic order, which is why long-range T OO ≈T N .…”
Section: Iii-results and Discussionmentioning
confidence: 99%
“…15. 1 The transition is first-order, and when phase segregation occurs at too low a temperature for atomic diffusion, it may be accomplished in a perovskite by cooperative oxide-ion displacements.…”
Section: I-introductionmentioning
confidence: 99%
“…These bonds promote local crystal structure distortions, which is the reason why the local Jahn-Teller orbital ordering is preserved. Indeed, the temperature of the charge and orbital ordering in Bi 0.5 Sr 0.5 MnO 3 is unusually high, above 500 K [23,24], whereas the characteristic temperature of charge and orbital ordering in the structures R 0.5 Sr 0.5 MnO 3 is 150 K [25,26]. Due to the local static Jahn-Teller distortions, the anisotropic character of the exchange interactions between the manganese ions persist.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest temperature phase seems to be either the CE phase, consisting of ferromagnetic zigzag chains with relative antiferromagnetic (AF) order (as in La 1/2 Ca 1/2 MnO 3 , where it was first proposed [2,3], and in Nd 1/2 Sr 1/2 MnO 3 [4] or Nd 1/2 Ca 1/2 MnO 3 [5]) or an A-type phase, i.e, ferromagnetic planes with relative AF alignment (as in Pr 1/2 Sr 1/2 MnO 3 [4]). The competition between the CE and A phases appears even in a simple one-orbital model [6] because of the interplay of ferromagnetic double-exchange and AF superexchange between the core t 2g spins of Mn (see also Fig.…”
mentioning
confidence: 99%